1981
DOI: 10.1038/291156a0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating human pituitary pro-γ-melanotropin enhances the adrenal response to ACTH

Abstract: The amino-terminal region of the common corticotropin/beta-lipotrophin (beta-LPH) precursor has been identified in the AtT-20 mouse tumor cells as a glycopeptide with an apparent molecular weight of 16,000 (the '16K fragment'). A third melanotropin core sequence or gamma-MSH similar to that found in ACTH and beta-LPH was predicted to occur in this glycopeptide from the complementary DNA sequence of mRNA isolated from bovine pituitary intermediate tissue. Recently, the mouse of 16K fragment has been found to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…The modulatory effects of pro-opiomelanocortin (POMC) products other than ACTH, particularly with reference to the N-terminal region, have been investigated by a number of workers, but with conflicting results. Although N-POMC has been shown to have a mild to moderate potentiating effect by some workers , Al-Dujaili et al 1981, such actions have not been confirmed by other studies (Pham-Huu-Trung et al 1982, Cathiard et al 1985.…”
Section: Introductionmentioning
confidence: 72%
“…The modulatory effects of pro-opiomelanocortin (POMC) products other than ACTH, particularly with reference to the N-terminal region, have been investigated by a number of workers, but with conflicting results. Although N-POMC has been shown to have a mild to moderate potentiating effect by some workers , Al-Dujaili et al 1981, such actions have not been confirmed by other studies (Pham-Huu-Trung et al 1982, Cathiard et al 1985.…”
Section: Introductionmentioning
confidence: 72%
“…When added alone to adrenal cells in vitro, it did not cause steroidogenesis but did promote RNA synthesis (Al Dujaili et al 1982). It also potentiated the steroidogenic activity of ACTH several-fold in perfused rat adrenal cells in vitro (Al Dujaili et al 1981). This potentiation was completely abolished in the presence of actinomycin D, indicating that the increase in RNA synthesis was linked to the potentiating activity of pro-γ-MSH (Al Dujaili et al 1982).…”
Section: Isolation and Characterisation Of Human Pro-γ-mshmentioning
confidence: 86%
“…The first reports for a role for these peptides appeared in the early 1980s (for a review see Harmer and Bicknell, 2005) when it was demonstrated that Lys-γ3-MSH and pro-γ-MSH, although not directly steroidogenic, have the ability both in vitro and in vivo to potentiate the steroidogenic response of the rat adrenal to ACTH (Figure 2) , Al-Dujaili et al 1981. This effect appears to correlate with the ability of both peptides to increase the activity of the enzyme Hormone Sensitive Lipase (HSL) .…”
Section: The Biological Role Of Gamma-mshmentioning
confidence: 99%